Efficacy and safety of SHR8554 on postoperative pain in subjects with moderate to severe acute pain following orthopedic surgery: A multicenter, randomized, double-blind, dose-explored, active-controlled, phase II/III clinical trial - Yanhua Zhao; Zhisheng Lu; Xuesong Song; Haihui Xie; Xungang Xiao; Guonian Wang; Qi Zhou; Qingmei Zhang; Liang Liu; Zhijian Lan; Ning Bai; Haiyan Wang; et al. (Pharmacological Research)
Biased µ-opioid receptor (MOR) agonists enhance pain relief by selectively activating G protein-coupled receptor signaling and minimizing β-arrestin-2 activation, resulting in fewer side effects. This multicenter Phase II/III trial evaluated the optimal dosage, efficacy, and safety of SHR8554, a biased MOR agonist, for postoperative pain management following orthopedic surgery. In Phase II, 121 patients were divided into four groups to receive varying patient-controlled analgesia (PCA) doses of SHR8554 or morphine. Phase III involved 320 patients with similar groupings, including a placebo group. The primary outcome was the resting summed pain intensity difference over 24 hours (rSPID24). Secondary outcomes included rSPID and active-SPID (aSPID) at other time points, rescue analgesia received, cumulative dose of analgesics, and satisfaction scores. Safety endpoints included treatment-emergent adverse events (TEAEs) and AE of special interest (AESIs). In both phases, SHR8554 demonstrated significant analgesic efficacy. In Phase II, the least squares (LS) mean differences in rSPID24 compared to morphine for the 0.05 mg,0.1 mg, and 0.2 mg SHR8554 groups were 16.8 (p = 0.01), 7.4 (p = 0.27), and 0.2 (p = 0.98), respectively. Phase III confirmed the efficacy of the 0.05 mg and 0.1 mg SHR8554 doses compared to placebo, with LS mean differences of 15.4 (p = 0.0001) and −19.8 (p < 0.0001), respectively. Trends in other secondary outcomes mirrored these findings. Safety analysis revealed that the 0.2 mg SHR8554 group had higher incidences of TEAEs (83.3 %) and AESIs (33.3 %) compared to other groups in Phase II. Similarly, in Phase III, the incidences of TEAEs were 81.0 %, 73.4 %, and 74.1 % in the 0.05 and 0.1 mg SHR8554 and morphine groups, respectively, compared with 61.3 % in the placebo group, while the AESIs were 29.1 %, 20.3 %, and 24.7 % compared with 12.5 % in the placebo group. In conclusion, SHR8554 exhibited efficacy compared to placebo and safety comparable to morphine for patients experiencing moderate-to-severe acute pain following unilateral total knee replacement or knee ligament reconstruction surgery. Trial Registration: Trial Name: Study on the Efficacy and Safety of SHR8554 Injection for Postoperative Analgesia in Orthopedics: Multicenter, Randomized, Double Blind, Dose Exploration, Placebo/Positive Control, Phase II/III Clinical Trial Registered on: chinadrugtrials.org.cn Identifier: CTR20220639.